Dental caries experience in 12-year-old schoolchildren in southeastern Brazil - Silvia Cypriano; Rosana H. S. Hoffmann; Maria da Luz R. de Sousa; Ronaldo S. Wada (University of São Paulo, 2008)
The aim of this study was to evaluate the prevalence of caries-free children using DMFT and significant caries (SiC) indexes in different caries prevalence groups in cities of the region of Campinas, São Paulo State, Brazil. The methodology proposed by the World Health Organization (1997) was used for caries diagnosis in 2,378 individuals. According to the DMFT index obtained in each evaluated city, 3 prevalence groups with representative samples were formed, being classified as low, moderate and high. SiC index was used to classify the one third of the population with the highest caries prevalence. In the low prevalence group, 32.4% of the children were caries free (DMFT=0), with mean DMFT of 2.29 and SiC index of 4.93. In the moderate prevalence group, 21.8% of the children were caries free, with mean DMFT of 3.36 and SiC of 6.74. Only 6.9% of the children in the high prevalence group were caries free and the mean DMFT was 5.54 (SiC=9.62). There was a great heterogeneity in dental caries distribution within the studied population, as well as a high caries prevalence considering the 3 classifications. Other indexes besides DMFT could be used to improve oral health assessment during establishment of the treatment plan and intervention.